Base initiated halogen-exchange reactions between perhaloalkanes - 傅伟敏 李兴亚 蒋锡夔 (Science China. Chemistry, 1997)
Halophilic attacks on C-X bonds (X=Br,Cl) by a base can easily initiate mtermolecular bromme-chlonne exchange reactions either among bromine-or chlorine-containing perhaloalkane molecules of different compounds of among molecules of the same compound It provides a new and convenient method to synthesize perhaloal-kanes Apparently,it pertains to an amomc mechanism,i e.the reaction is initiated by halophilic attack on C-X bonds by the base,and an intermediate carbanion is formed.Distributions of the products depend on the equilibria involving all carbanion intermediates and perhaloalkane product molecules.